2016
DOI: 10.1002/bem.21998
|View full text |Cite
|
Sign up to set email alerts
|

A short‐term extremely low frequency electromagnetic field exposure increases circulating leukocyte numbers and affects HPA‐axis signaling in mice

Abstract: There is still uncertainty whether extremely low frequency electromagnetic fields (ELF‐EMF) can induce health effects like immunomodulation. Despite evidence obtained in vitro, an unambiguous association has not yet been established in vivo. Here, mice were exposed to ELF‐EMF for 1, 4, and 24 h/day in a short‐term (1 week) and long‐term (15 weeks) set‐up to investigate whole body effects on the level of stress regulation and immune response. ELF‐EMF signal contained multiple frequencies (20–5000 Hz) and a magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 44 publications
1
7
0
1
Order By: Relevance
“…Different experimental periods and durations and severities of the electromagnetic eld in these studies may lead to discrepancies. Moreover, similar to our study, ELF-EMF exposure has been shown to decrease CRH and proopiomelanocortin gene expression, hence CORT synthesis in mice [de Kleijn et al, 2016]. It is suggested that decreased anxiety-and depression-like behaviors in the S-EMF offspring are probably due to decreased serum CORT levels [Gregus et al, 2005b].…”
Section: Discussionsupporting
confidence: 86%
“…Different experimental periods and durations and severities of the electromagnetic eld in these studies may lead to discrepancies. Moreover, similar to our study, ELF-EMF exposure has been shown to decrease CRH and proopiomelanocortin gene expression, hence CORT synthesis in mice [de Kleijn et al, 2016]. It is suggested that decreased anxiety-and depression-like behaviors in the S-EMF offspring are probably due to decreased serum CORT levels [Gregus et al, 2005b].…”
Section: Discussionsupporting
confidence: 86%
“…In mice exposed to 10 μT ELF-MF (1, 4, or 24 h/day for 1 week—short-term exposure), no significant differences in CRH gene expression in hypothalamus were observed, whereas ACTH plasma level was lower regardless of the daily exposure time (1, 4, or 24 h/day for 1 week). Moreover, the expression of pituitary level of POMC was lower in an exposure time-dependent manner, and a statistically significant decrease appeared after 24 h/day exposure [ 124 ]. Mostafa et al [ 125 ] showed that 2- and 4-week exposure of rats to ELF-MF (2 G, equivalent to 0.2 mT) significantly increased their plasma corticosterone level.…”
Section: Elf-mf-induced Changes In Levels Of Neurotransmitters Homentioning
confidence: 99%
“…Thus, the ELF-MF exposure can cause deregulation of the immune system, thereby increasing vulnerability to infectious and autoimmune diseases. Interesting results concerning the effect of ELF-MF on lymphocytes level were obtained by de Kleijn et al [ 124 ]. In mice exposed to 10 μT ELF-MF (1, 4, or 24 h/day for 1 week—short-term exposure, or for 15-week long-term exposure) the increase in CD3+/CD4+ T-lymphocytes was observed only after short-term exposure to ELF-MF.…”
Section: Elf-mf-induced Changes In Levels Of Neurotransmitters Homentioning
confidence: 99%
“…An increased risk of amyotrophic lateral sclerosis (ALS) in workers occupationally exposed to ELF-MFs were observed in Huss, et al [21]. Kleijn, et al [22]; Zhang, et al [23]; Schüz, et al [24]; Tang, et al [25]; Fixler, et al [26]; Wang, et al [27]; Prato, et al [28]; Corbacio, et al [29]; Vanderstraeten and Gillis [30]; Bowman, et al [31]; Prato, et al [32]; Burda, et al [33]; Burger, et al [34] reported the other biological effects of ELF-MFs (0 to 300 Hz) fields. Smith, et al [58]; Lednev [59]; Blanchard and Blackman [60]; Binhi [61] proposed the mechanisms of biological effects of ELF-MFs which are cyclotron resonance theory and it's new interpretation,the ion parametric resonance model and an interference of ions bound within proteins.…”
Section: The Hyperfine Coupling Mechanism Of Biological Effects On Elmentioning
confidence: 99%
“…For example, more and more people have been attracted by the small increases in childhood leukemia for children living near power lines and possible increases in brain tumors for heavy use of cell phones [1]. The biological effects of extremely low-frequency (0 to 300 Hz) magnetic fields (ELF-MFs) are presented [21][22][23][24][25][26][27][28][29][30][31][32][33][34]. The biological effects of intermediate frequency (300 Hz to 100 kHz) magnetic fields(IMF-MFs)are discussed [35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%